Electronic Dissertations in the Netherlands - Klugkist, Alex C. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
Several Dutch university libraries started full text electronic storing and publishing of scholarly information during the first half of the nineties; they aimed to build up collections of full text digital information and to develop digital user services. Doing so, they wanted to acquire expertise in the areas of producing, converting, indexing and providing electronic documents. The University of Groningen decided to concentrate in the first instance on dissertations (and other university publications), because these documents are quality controlled and free of copyright. At this university each year about 200 dissertations are submitted in all kind of disciplines. From January 1994 Ph D. students were allowed to present an electronic version of their dissertation to the University Library Groningen for interlibrary exchange instead of 50 printed copies.